Implementation of Speech to-Text Application for Deaf Students on Inclusive Education Course - Irdamurni, Irdamurni; Taufan, Johandri (Department of Special Education, 2019)
Inclusive education is an educational services system where people with disabilities can attend to the nearest regular school of their place, included college. Persons with hearing impairment is one of the minorities who is still marginalized from the right, including the needs of access to communications and information technology. Because of that, people with hearing impairment are not able to participate in instructional activities. Based on the observation and the interview, to graduate and undergraduate students with hearing impairment of Special Education department, they said that they still have problems in communicating with lecturers or other students, because of their inability to understand the explanation of the lecturer. This paper aims at providing an analysis of using speech to text app in an inclusive education course, which can record the voice of a lecturer and converted to text that is displayed through the power point, so that, the students with hearing impairment can read the text when the learning occurred. A classroom action research with tw0 cycle is used to recognize a summary of the instructional which attended by two students with hearing impairment and twenty-eight regular students. Observation, test, and interview conducted by team teaching show that speech to text based on power point has an impact in increasing comprehension of students with hearing impairment on inclusive education course.